UH-1N Category II Arctic Tests. Appendix IV. Volume II. - Ladegard, Paul E. (1972)
Contents: Cargo Hook Evaluation; XM-94 Weapons System Checkout; and Propulsion System Evaluation. Appendix 4, Volume 2 to Rept. no. AFFTC-TR-72-10 dated Mar 72, AD-894 512L. See also Volume 1, AD-901 649L.